Islamic Education Media in Hadith - Junida Fitriani Sitorus; Zulfahmi Lubis; Ida Marina Harahap; Nurul Liza Nasution; Raisa Nur Salun (Universitas Muhammadiyah Enrekang, 2023)
The educational media utilized by Prophet Muhammad (SAW) reflects a holistic approach in delivering Islamic teachings. Prophet Muhammad employed various media, including two-dimensional and three-dimensional visual aids such as charts, graphs, posters, images, and maps, as well as projected aids like films, slides, and PowerPoint presentations. Furthermore, he distinguished media based on their material nature, comprising tangible items such as the Qur'an, elements of nature, depictions of the worldly and afterlife scenes, and intangible elements like exemplary behavior, directives, and rewards or punishments.Educational media not only varies in form but also encompasses observable objects, images, lines, and the evolution of modern educational media like video, audio, and films. In the context of learning, the presence of media plays a crucial role in facilitating material delivery, simplifying complex concepts, and aiding the understanding of learners. This approach, as applied by Prophet Muhammad, provides insights for the development of improved and relevant Islamic educational media within the modern educational context.